ANALYSIS OF THE EFFECT OF SERVICE QUALITY ON PATIENT SATISFACTION IN RSUD ACEH TAMIANG - Saiful Lizan; T. Edyansyah T. Edyansyah; Rusydi Rusydi; Heriyana Heriyana (PT. Radja Intercontinental Publishing, 2022)
The purpose of this study was to identify and analyze the effect of service quality on patient satisfaction. The object of this research is RSUD Aceh Tamiang. This study uses a sampling technique using accidental sampling, which is a technique of determining the sample by chance, meaning that anyone who meets the researcher can be used as a sample. The analysis in this study uses multiple linear regression analysis, the results of this study indicate that partially tangible, realibility, responsiveness, assurance, and empathy variables have a positive and significant effect on patient satisfaction at RSUD Aceh Tamiang. The results of this study indicate that the tangible, realibility, responsiveness, assurance, and empathy variables simultaneously have a positive and significant effect on patient satisfaction at RSUD Aceh Tamiang.